Risks and Realities of Delayed Splenic Bleeding. Issue 8 (August 2019) - Kratzke, Ian M.; Strassle, Paula D.; Schiro, Sharon E.; Meyer, Anthony A.; Brownstein, Michelle R.
Delayed splenic bleeding (DSB) is a poorly understood complication of blunt splenic injury. Treatment for splenic bleeding may involve splenectomy, but angioembolization is becoming a widely used adjuvant for management. Using the North Carolina Trauma Registry, this study aimed to evaluate the incidence, mortality, and risk factors for DSB in North Carolina. Using ICD-9 and ICD-10 codes, patients were stratified into two cohorts, those who underwent immediate splenectomy and those who were initially managed nonoperatively. DSB was then defined as splenectomy at greater than 24 hours after presentation. Of the 1688 patients included in the study, 269 patients (16%) underwent immediate splenectomy and 1419 (84%) were managed nonoperatively initially, with 32 (2%) having delayed splenectomy. Older age (≥30 years) was associated with increased odds of having delayed splenectomy (odds ratio 4.30; 95% confidence interval 1.08, 17.17; P = 0.04). Four per cent of patients managed nonoperatively and undergoing an angioembolization procedure eventually required splenectomy. Risk factors for DSB remain elusive. Splenic artery embolization may be used as an adjuvant to splenectomy for stable patients, but it is not always a definitive treatment, and patients may still require splenectomy.